Performance Expectancy in AR/VR Technology Adoption in Tourism Industry: A Systematic Literature Review - Rahmad, Muhammad; Rachman , Arief Faisal (Jurnal Locus Penelitian dan Pengabdian, 2025)
Despite their significant potential, AR/VR adoption rates vary considerably across different contexts, with developing countries like Indonesia showing a 29% adoption gap compared to developed nations. This study systematically analyzes the role of performance expectancy in AR/VR technology adoption within the tourism sector through a comprehensive literature review spanning 2015–2024. A systematic literature review following PRISMA protocols was conducted across Scopus, Web of Science, and Google Scholar databases, with inclusion criteria encompassing English- and Indonesian-language articles published between 2015 and 2024 that focused on performance expectancy and AR/VR adoption in tourism contexts. From 532 initially identified articles, 42 met all inclusion criteria and underwent systematic analysis using thematic content analysis and meta-synthesis approaches. The synthesis reveals that performance expectancy emerges as the strongest predictor of AR/VR adoption, contributing 46%–70% of variance in adoption decisions, operationalized through four primary dimensions: utilitarian value, relative advantage, job-fit, and outcome expectations. AR/VR adoption is measured through usage intensity, system integration, implementation scope, and utilization level, with organizational technology readiness and risk perception serving as critical moderators. Significant contextual differences exist between developed and developing countries in AR/VR adoption patterns, with substantial research gaps identified in the Indonesian context—particularly the scarcity of empirical studies on AR/VR adoption in travel agencies. Future research should explore Indonesia-specific contexts, moderator roles (including organizational size and technology type), and mixed-method approaches to understand the complexity of AR/VR adoption in tourism.